Sistemática e zoogeografia do gênero Tomopterus Audinet-Serville, 1833 (Coleoptera, Cerambycidae, Cerambycinae, Rhinotragini) - Magno, Paulo Roberto (1994)
The neotropical genus Tomopterus Audinet-Serville, 1833, is revised. Six groups of species, based on comparative study of the external morphology and male terminalia, are proposed: bispeculifer group (T. rufotibialis, T. bispeculifer, T. roppai); basimaculatus group (T. basimaculatus); albopilosus group (T. albopilosus, T. grossefoveolatus); obliquus group (T. flavofasciatus, T. obliquus, T. servillei, T. consobrinus, T. longicornis); quadratipennis group (T. clavicornis, T. quadratipennis, T. exilis, T. tetraspilotus, T. pictipennis); staphylinus group (T. staphylinus, T. seabrai, T. aurantiacosignatus, T. similis, T. vespoides, T. larroides). Five species are considered as new (in press): T. roppai, sp. n., T. servillei, sp. n., T. clavicornis, sp. n., T. seabrai, sp. n., from Brazil and T. tetraspilotus, sp. n., from Brazil and Peru. A new combination is established (in press): T. rufotibialis (Zajciw, 1968), comb. n. (from Epimelitta). The available biological data are summarized. Keys to the species and species-groups as well as a checklist of the species belonging to each group are provided. The twenty-two known species and fifteen male terminalia are illustrated. Maps of hitherto known geographical distribution of the species are included.